Keutel syndrome: Report of two novel MGP mutations and discussion of clinical overlap with arylsulfatase E deficiency and relapsing polychondritis. Issue 4 (23rd January 2014) - Weaver, K. Nicole; El Hallek, Moussa; Hopkin, Robert J.; Sund, Kristen L.; Henrickson, Michael; del Gaudio, Daniela; Yuksel, Adnan; Acar, Gül Ozbilen; Bober, Michael B.; Kim, Jinoh; Boyadjiev, Simeon A.
<x xml:space="preserve">Abstract</x> Keutel syndrome is a rare, autosomal recessive disorder characterized by diffuse cartilage calcification, peripheral pulmonary artery stenosis, midface retrusion, and short distal phalanges. To date, 28 patients from 18 families have been reported, and five mutations in the matrix Gla protein gene (MGP) have been identified. The matrix Gla protein (MGP) is a vitamin K‐dependent extracellular protein that functions as a calcification inhibitor through incompletely understood mechanisms. We present the clinical manifestations of three affected siblings from a consanguineous Turkish family, in whom we detected the sixth MGP mutation (c.79G>T, which predicts p.E27X) and a fourth unrelated patient in whom we detected the seventh MGP mutation, a partial deletion of exon 4. Both mutations predict complete loss of MGP function. One of the patients presented initially with a working diagnosis of relapsing polychondritis. Clinical features suggestive of Keutel syndrome were also observed in one additional unrelated patient who was later found to have a deletion of arylsulfatase E, consistent with a diagnosis of X‐linked recessive chondrodysplasia punctata. Through a discussion of these cases, we highlight the clinical overlap of Keutel syndrome, X‐linked chondrodysplasia punctata, and the inflammatory disease relapsing polychondritis. © 2014 Wiley Periodicals, Inc.